Meneropong Spiritualitas Disabilitas bagi Keadilan Disabilitas - Paulus Eko Kristianto (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2022)
Abstract:Disability spirituality is part of the study of disability theology. Disability justice is the hope of all persons with disabilities. The problem that arises is how does disability spirituality enable disability justice? This article tries to formulate this model based on literature research in related books and journals. The results of the study show that spirituality with disabilities at least touches their relationship with themselves, others, and God. This relationship is integrative and related to each other. This insight into disability spirituality is expected to give birth to disability justice by enriching the scientific community in the field of disability theology and the formation of disability spirituality in faith communities. Abstrak: Spiritualitas disabilitas menjadi bagian dari kajian teologi disabilitas. Keadilan disabilitas merupakan harapan semua penyandang disabilitas. Persoalan yang muncul ialah bagaimana spiritualitas disabilitas memungkinkan keadilan disabilitas? Artikel ini mencoba merumuskan model ini dengan berpijak dari penelitian pustaka terhadap buku dan jurnal terkait. Hasil penelitian menunjukkan spiritualitas disabilitas sekurangnya menyentuh relasinya dengan diri sendiri, orang lain, dan Tuhan. Relasi ini bersifat integratif dan berkaitan satu sama lain. Peneropongan spiritualitas disabilitas ini diharapkan melahirkan keadilan disabilitas dengan memperkaya keilmuan rumpun bidang teologi disabilitas dan formasi spiritualitas disabilitas di komunitas iman.